1985
DOI: 10.1037/0735-7044.99.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress and prepuberal social rearing conditions interact to determine sexual behavior in male rats.

Abstract: The two major categories of factors known to influence adult sexual behavior potentials are the relative amounts of androgen present during specific stages of perinatal ontogeny and adequate social stimulation during prepuberal development. The possible interaction between these two was evaluated by characterizing the ejaculatory and lordotic behavior potentials of prenatally stressed and control male rats that had been weaned at 16 days of age and raised either in total social isolation or with a same-age fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
4

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 26 publications
5
28
4
Order By: Relevance
“…The postweaning period may be especially sensitive to disruptions of the social environment because social experience during this critical period is required for normal development. Postweaning social isolation within a critical preadolescent time window leads to long-term effects on social behaviors, including behaviors that rely on the MeA, such as sexual mounts/intromissions and non-contact penile erections, social aggression and avoidance, defensive response patterns during social aggression, and reduced social vocalizations (Ward and Reed, 1985;Bakker et al, 1995;Wongwitdecha and Marsden, 1996;Pellis et al, 1999;Cooke et al, 2000;Lukkes et al, 2009;Shoji and Mizoguchi, 2011;Seffer et al, 2015), and other behaviors (Hall et al, 1997(Hall et al, , 1998Varty and Geyer, 1998;Bakshi and Geyer, 1999;Makinodan et al, 2012). Effects of postweaning social isolation on these social behaviors may be mediated by the MeA.…”
Section: Discussionmentioning
confidence: 99%
“…The postweaning period may be especially sensitive to disruptions of the social environment because social experience during this critical period is required for normal development. Postweaning social isolation within a critical preadolescent time window leads to long-term effects on social behaviors, including behaviors that rely on the MeA, such as sexual mounts/intromissions and non-contact penile erections, social aggression and avoidance, defensive response patterns during social aggression, and reduced social vocalizations (Ward and Reed, 1985;Bakker et al, 1995;Wongwitdecha and Marsden, 1996;Pellis et al, 1999;Cooke et al, 2000;Lukkes et al, 2009;Shoji and Mizoguchi, 2011;Seffer et al, 2015), and other behaviors (Hall et al, 1997(Hall et al, , 1998Varty and Geyer, 1998;Bakshi and Geyer, 1999;Makinodan et al, 2012). Effects of postweaning social isolation on these social behaviors may be mediated by the MeA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fostering of PS rats to control mothers, i.e., suckling with a previously nonstressed dam, prevented the longlasting effects on body weight, motor activity and emotionality. Many authors have shown that early rehabilitation from some prenatal deleterious influences may improve physical and behavioral development in postnatal life (10,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on prenatal stress provides information about the effects of several predictable and unpredictable models of repeated strong stresses (5,(10)(11)(12). Nonetheless, the effects of chronic exposure to mild variable stresses during prenatal life and the influence of cross-fostering of prenatally stressed pups to nonstressed dams have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that maternal restraint stress in the 3rd week of pregnancy, in both mice and rats, demasculinized and feminized the sexual behavior of male offspring (Holson, Gough, Sullivan, Badger, & Sheehan, 1995). Prenatal stress was associated with disruptions in the normal course of sexual differentiation and subsequent alterations in reproductive behavior (Rhees & Fleming, 1981), such as impaired ejaculatory behavior and increased female lordotic behavior in male offspring of stressed pregnant rats (I. L. Ward, 1972;I. L. Ward & Reed, 1985).…”
Section: Effects Of Prenatal Stress On Behavior Of Rodent Offspringmentioning
confidence: 99%